2021
DOI: 10.1007/s12144-021-01661-3
|View full text |Cite
|
Sign up to set email alerts
|

Self-serving social strategies: A systematic review of social cognition in narcissism

Abstract: Narcissistic Personality Disorder is characterised by inflated self-importance, an excessive need for admiration, and a lack of empathy. The interpersonal difficulties associated with narcissistic personality may be becoming more widespread given its increasing prevalence within the general population. This systematic review investigated the relationship between narcissistic personality traits and social cognition (i.e. theory of mind; emotion recognition; empathy; emotional intelligence) in clinical and non-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 169 publications
3
14
0
Order By: Relevance
“…Notably, greater narcissistic tendencies in dimensions such as acclaim seeking and manipulativeness were associated with a higher number of faces judged as real. This is in line with recent research which found people with higher narcissism scores less likely to engage in analytical reasoning strategies such as reflective thinking (Ahadzadeh et al, 2021;Littrell et al, 2020), and to be more vigilant and attentive to external stimuli (Carolan, 2017;Eddy, 2021;Grapsas et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Notably, greater narcissistic tendencies in dimensions such as acclaim seeking and manipulativeness were associated with a higher number of faces judged as real. This is in line with recent research which found people with higher narcissism scores less likely to engage in analytical reasoning strategies such as reflective thinking (Ahadzadeh et al, 2021;Littrell et al, 2020), and to be more vigilant and attentive to external stimuli (Carolan, 2017;Eddy, 2021;Grapsas et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…This apparent discrepancy probably stems from the fact that this study is the first to examine and replicate the relationship between actual performance at perspective taking and narcissism in two non-clinical samples. Further, the finding that narcissists pay a lot of attention to others is actually very much in line with many major theoretical models of the functioning of highly narcissistic individuals and support the emerging view that narcissists may lack the communal motives rather than the abilities (e.g., Eddy, 2021). Whichever explanations of the reduced egocentrism of narcissists is correct, our findings reveal how little we know about narcissists' social cognition in the interpersonal domain.…”
Section: Discussionsupporting
confidence: 88%
“…The few studies that uses performance-based measures offer a more nuanced picture (for a review, see also Eddy, 2021): Konrath and collaborators (Konrath et al, 2014) showed that high narcissism individuals were more competent than low narcissism individuals in recognizing other people's emotional facial expressions, but another study reported that narcissism predicted lower performance at guessing mental states from facial expressions (Vonk et al, 2013). In the same line, Burgmer et al (2021) found a negative association between vignette-based empathy and narcissism, but Hepper and collaborators (Hepper, Hart, Meek, et al, 2014) found that empathy towards a distressed person could be increased in highly narcissistic individuals by explicitly instructing them to imagine what the other person is feeling.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, impulsive non-conformity, whereby individuals with schizophrenia express strong opposition to convention and the opinions or expectations of others, even where this would seem harmful or irrational, may enhance cognitive self-other distinction. Similar characteristics can be seen in NPD, where rivalry and entitlement emphasize one's own uniqueness, and deception may be used to maintain differentiation between the cognitive mental states of self and other ( 152 ).…”
Section: Relevance Of Self-other Distinction To Psychiatrymentioning
confidence: 80%